Students Perception of Using the Duolingo Application in Mastering English Language Skills in an English Study Program - Sofian, Muhammad; Ilham, Ilham; Bafadal, Moh. Fauzi (English Education Department, 2025)
This research aims to analyze the effect of using the Duolingo application on students' mastery of English in the English Education Study Program at one of the universities in Indonesia. A quantitative approach was used in this study, using data collection methods through a Likert scale-based questionnaire adopted from scientific articles. Respondents were selected using a purposive sampling technique, using the criteria of students who have used the Duolingo application for at least one month. The questionnaire consisted of closed-ended statements that measured the intensity of Duolingo application usage and students' English mastery level, including vocabulary, reading, writing, listening, and grammar skills. Data were analyzed using simple linear regression to determine the relationship between the independent variable (intensity of Duolingo usage) and the dependent variable (English language acquisition). The results showed that using the Duolingo application significantly influences students' mastery of English. Duolingo allows students to learn independently outside of class in a more fun and interactive way and improve their English skills effectively. This finding indicates that Duolingo can be used as an effective supplementary learning medium in the context of English language education